Evaluation of outcome of laparoscopic ventral hernia repair - Mahbuba Khatun; Afroza E Alam; Muhammad Moinul Hossain; Fatama Akter Chowdhury; A K M Ariful Islam; Iffat Sharmin (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: The repair of ventral hernia has evolved from simple suture approximation to the use of prosthetic mesh and recently laparoscopic procedures. Now a day’s ventral hernia repair is increasingly performed laparoscopically. But Complications rate with this procedure are not well characterized. Objective: To evaluate the outcome of laparoscopic ventral hernia repair. Method: This prospective observational study was conducted in the department of surgery, Bangladesh Medical University, Shahbag, Dhaka, during the period of June 2018 to July 2019. The calculated sample size was 28, but due to less availability of patient, time constraint and costly procedure total 18 patients with ventral hernia were selected. Signed informed consent were obtained from all patients, Laparoscopic intraperitoneal only mesh technique was applied and composite mesh was used. All patients were followed post operatively. A predesigned questionnaire was formed for collecting data. Results: Most patients were found in the age group 41 – 50 years. Mean age of the patients was 41 ± 7.42 years. 13 patients (72.22%) were female and 5 patients (27.78%) were male. Umbilical, Para umbilical and incisional hernia were observed in 2(11.11%), 4(22.22%) and 12(66.67%) patients respectively. Mean ±SD time for operative procedure was 82.6 ± 19.10. 1 (5.5%) patient had been suffering from gut injury. Total 5 patients (27.61%) had been suffering from postoperative complications. postoperative Ileus developed in 2 (11.11%) patients, Seroma, port site and mesh site infection were observed in 1 (5.5%) patient individually. According to visual analogue scale post operatively pain was assessed and shown to decline gradually. AT 30th POD follow up, 1 patient (5.6%) felt mild pain and 17 patients (94.44%) felt no pain over surgical site. Mean hospital stay was 4 ± 3.39 days. Mean of return to activity was 5.6±2.17. Conclusion: From this study it can be concluded that laparoscopic ventral hernia repair is an effective procedure and can be performed as short stay surgery. It provides much benefit with low complications. This technique can be safely applied in the patients suffering from ventral hernia. J Shaheed Suhrawardy Med Coll 2024; 16(2): 99-102